Marketing channel and cost analysis of selected vegetables in Benguet and Mountain Province (The Philippine Journal of Crop Science, 2010)
The study assessed the marketing service performance of Cordillera farmers and traders as measured by the cost per unit of carrying out the various functions on marketing vegetable products. Specifically, the costs of transportation and losses by type of product and type of marketing participants were compared and rationalized based on the respective marketing services performed. Farmers sell their vegetables (through the commission agents, assembler, assembler-wholesalers or direct sales) to La Trinidad Vegetable Trading Post or Hangar market in Baguio City. The Cordillera consumers (including visitors) purchase about 11.10% of the total vegetables traded in any given day. A large proportion of the Cordillera Vegetables are brought to Manila markets (60.97%) while the rests are transported to Urdaneta market in Pangasinan (15.73%) and other markets (12.20%) outside of Metro Manila. Wholesalers in La Tinidad are very important outlets of the Cordillera farmers as they directly absorb 23.30% of the total traded vegetables. Volume-wise, assemblers are the next most popular outlet of the farmers. Retailing activities are heavy in Hangar markets compared to La Trinidad since most consumers are accustomed to buying their vegetables from the Hangar market, which they consider as “consumer market”. High transport costs and losses due to transit are cited by both farmers and traders as their most pressing problem. Lack of market and market information is a major concern among farmers. Marketing costs can be reduced through the government initiative to rehabilitate farm to market roads and providing technical assistance to improve product packaging. A market information and dissemination services (MIDS) must strictly be implemented to enable the actors in the marketing system to be more efficient in their decision making processes.